Diseño e Implementación de un Sistema de Supervisión y Control para el Proceso de Vidrio Laminado para la Planta AGP Colombia de Bogotá. - Amaya Guevara, Brayan David; Virviescas Rincon, Jhon Sebastian (Universidad Antonio Nariño, 2023)
This project proposes the development of a monitoring and control system for the variables: temperature, pressure and vacuum, of a laminated glass manufacturing process for the AGP Colombia plant in the city of Bogota, taking into account analog and digital signals involved in the process for the autoclave 034 machine